PENGARUH INVESTASI DALAM NEGERI, INVESTASI ASING, TENAGA KERJA DAN INFRASTRUKTUR TERHADAP PEREKONOMIAN DI PROVINSI SUMATERA BARAT - Tevi Mahriza; Syamsul Amar B (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to determine the effect of economic variables on economic growth in West Sumatra. The type of data in this study is time series. In analyzing sequential data from 1987 to 2017, OLS Analysis method was used. Based on the results of testing of domestic investment, foreign investment, labor and road infrastructure have a significant positive effect on the economic growth of West Sumatra. Where domestic investment and foreign investment is an investment that will drive the economic wheel of West Sumatra, labor will increase the economic productivity of West Sumatra and road infrastructure as public goods will drive the economic wheel as a means of connecting in the distribution of goods and services in West Sumatra